Professional training of future fine arts teachers for the use of graphic design - Wang Wei (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2023)
The article is devoted to the urgent problem of training future fine arts teachers for the use of graphic design. The goal of the article is to systematize and generalize scientific research on the training of future fine arts teachers for the use of graphic design. It was specified that in modern society the issues of forming the professional qualities of the art teacher, creating the conditions that would ensure their training in the system of higher pedagogical education are becoming particularly acute. After all, nowadays there is a need to develop design skills and mastery in future art teachers who could use graphic design in their professional activity, as well as teach this craft to students so that they can create brochures, magazines, books, advertising products, various packaging, web design etc. It has been proven that the training of such specialists who have the basics of design culture is an urgent problem of modern art pedagogy. It was determined that the formation of design skills in students as an integral component of the professional qualities of a future teacher of fine arts is realized in the process of their activity, during which individual characteristics are manifested, which contribute to the formation of a person’s positive attitude towards their profession and the people with whom they work, as well as the desire for personal growth and professional improvement. In general, the training of future fine arts teachers for the use of graphic design is a long, controlled, responsible process of forming professional competences, the result of which is knowledge and skills that future specialists will use in their further activities; it is the unity of theoretical and practical readiness of future teachers of fine arts to use graphic design in their professional activities. It has been confirmed that proper training of future art teachers with established professional competences will provide opportunities to become competitive in the service market.